Mechanical Properties of Thin and Thick Coatings Applied to Various Substrates - et. al., Kyaw Ye Ko, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this work, theoretical and experimental studies have been carried out to determine the Young's modulus of materials for coatings applied to substrates. It is shown that residual stresses are generated inside thin and thick coatings deposited on a substrate. As a result of these stresses, the strip of the two-layer material is assumed to have some curvature. With the help of bending theory, it was substantiated that the bending stiffness of two-layer materials is a function of the initial radius of curvature generated by residual stresses, the mechanical radius of curvature arising during bending tests, mechanical (Young's modulus) and geometric (width and thickness) characteristics of two-layer systems. The corresponding expression was converted to a second or third order equation to calculate the Young's modulus of the coating undergoing residual stresses.